An introduction to Object-Oriented programming with Java - Wu, C. Thomas (Mc Graw Hill, 2001)
An Introduction to Object-Oriented Programming with Java" provides an accessible and technically thorough introduction to the basics of programming using Java. The fourth edition continues to take a truly object-oriented approach. Objects are used early so that students think in objects right from the beginning. In the fourth edition, the coverage on defining classes has been made more accessible. The material has been broken down into smaller chunks and spread over two chapters, making it more student-friendly. Also, new to this edition is the incorporation of Java 1.5 features, including use of the Scanner Class and the Formatter Class. The hallmark feature of the book, Sample Development Programs, are continued in this edition. These provide students with an opportunity to incrementally, step by step, walk through program design, learning the fundamentals of software engineering. Object diagrams, using a subset of UML, also continue to be an important element of Wu's approach. The consistent, visual approach assists students in understanding concepts.